PENGARUH PROMOSI DAN E-SERVICE QUALITY TERHADAP MINAT BELI PADA SITUS BELANJA ONLINE LAZADA - Ni Putu Yuli Sariyanti; , I Gusti NG A Gede Eka Teja Kusuma; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Lazada is an e-commerce with a marketplace concept that provides many facilities needed by sellers and buyers in conducting online buying and selling transactions. In order to survive in the midst of many e-commerce, companies must strive to learn and understand the needs and desires of their customers, so that they can generate a sense of interest in buying consumers. This study aims to determine the effect of promotion and e-service quality on buying interest. The population in this study is Lazada consumers in the Denpasar City area who know and actively use Lazada e-commerce. The sampling technique used purposive sampling method. The data analysis technique used to test the hypothesis is multiple linear regression analysis. The results showed that the promotion and quality of e-service had a positive and significant effect on Lazada consumers' buying interest. Further researchers are expected to add variables other than promotion and e-service quality, because there are other factors that can influence buying interest.